The Effect Of Workload And Work Environment On Employee Performance With Job Satisfaction As A Mediator - Mandala, Achmad Surya; Kisman, Zainul; Kanto, R. Dwi Sunu; Trisilo, Rudi Bambang (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri, 2025)
This study investigates the influence of workload and work environment on employee performance with job satisfaction as a mediating variable in the Directorate General of Training and Productivity Development, Ministry of Manpower of Indonesia in 2025. Using a quantitative approach, data were collected through structured questionnaires from 100 civil servants selected by convenience sampling. Structural Equation Modeling (PLS-SEM) was employed to analyze relationships among variables. Results indicate that workload positively affects both job satisfaction and employee performance, while the work environment significantly influences job satisfaction but does not directly affect performance. Job satisfaction plays a critical mediating role in linking workload and work environment to performance outcomes. The findings underline that an appropriate workload and supportive work environment enhance employee satisfaction, which in turn boosts performance. This study highlights the importance of managing workload and workplace conditions to improve public sector employee productivity. Limitations include a single-agency focus and cross-sectional design. Future research should explore broader contexts using longitudinal and probabilistic sampling methods.